The Genetics of Chronic Itch: Gene Expression in the Skin of Patients with Atopic Dermatitis and Psoriasis with Severe Itch - Nattkemper, Leigh A; Tey, Hong Liang; Valdes-Rodriguez, Rodrigo; Lee, Helen; Mollanazar, Nicholas K; Albornoz, Christian; Sanders, Kristen M; Yosipovitch, Gil (Journal of investigative dermatology, 2018)
To identify itch-related mediators and receptors that are differentially expressed in pruritic skin, we used RNA sequencing to analyze the complete transcriptome in skin from paired itchy, lesional and nonitchy, nonlesional skin biopsies from 25 patients with atopic dermatitis and 25 patients with psoriasis and site-matched biopsies from 30 healthy controls. This analysis identified 18,000 differentially expressed genes common between itchy atopic and psoriatic skin compared with healthy skin. Of those, almost 2,000 genes were differentially expressed between itchy and nonitchy skin in atopic and psoriatic subjects. Overexpression of several genes, such as phospholipase A2 IVD, substance P, voltage-gated sodium channel 1.7, and transient receptor potential (TRP) vanilloid 1, in itchy skin was positively correlated with itch intensity ratings in both atopic dermatitis and psoriasis. Cytokines such as IL-17A, IL-23A, and IL-31 had elevated gene transcript levels in both itchy atopic and psoriatic skin. However, expression of genes for TRP vanilloid 2, TRP ankyrin 1, protease-activated receptor 2, protease-activated receptor 4, and IL-10 was found to be increased only in pruritic atopic skin, whereas expression of genes for TRP melastatin 8, TRP vanilloid 3, phospholipase C, and IL-36α/γ was elevated only in pruritic psoriatic skin. This "itchscriptome" analysis will lead to an increased understanding of the molecular mechanisms of chronic pruritus and provide targets for itch treatment irrespective of disease state.